Reconfiguring the relationship between the ‘good (hetero)sexual subject’ and the grey area between sex and rape - Hansen, Maria (Sexualities, 2025)
Though many advocates argue that ‘rape is rape’, empirical research demonstrates that many incidents and experiences are ambiguous. This article explores how heterosexual norms play into the construction of a grey area between ‘just sex’ and rape. Based on an analysis of 30 interviews with Norwegian men and women about alcohol-related heterosexual encounters, the article explores how such encounters can become ambiguous. There is a mutually constitutive relationship between what is ‘normal’ and what is not. Simultaneously, heterosexuality and sexual norms are fluid, contextual and constantly developing, so when norms regulating ‘normal’ sex shift, transgressions from these norms probably do as well. By using Gavey’s (2005) model of normative heterosexuality as a scaffold that supports rape culture as a heuristic device, I examine these stories of alcohol-related heterosexual encounters to investigate how norms about heterosexual sex are involved in how people constitute themselves as ‘good sexual subjects’ today. Based on these findings, I discuss how the pathway to becoming a good sexual subject may simultaneously lead into murky and ambiguous territory.